The Causal Relationship Model of The Happiness of the Working Elderly within Career Groups - Chuayounan, Satit (International Journal of Multidisciplinary in Management and Tourism, 2022)
The objectives of this research were to study the causal relationship model of the happiness of the elderly working within career groups. The sample included 260 elderly people who were members of career groups in Phayao Province, Thailand. A questionnaire that employed a five-point rating scale was used for data collection. Descriptive statistics including frequency, percentage, mean and standard deviation were used to analyze the basic data, and the Structural Equation Modeling (SEM) with AMOS was used to analyze the causal model. The testing results of the structural modeling fit with the hypothesis model (c2 = 51.342, df = 28, c2/df = 1.834, RMR = 0.030, GFI = 0.963, AGFI = 0.927, CFI = 0.965, RMSEA = 0.047), and the research findings indicated that 1) Perception of self-efficacy in work has a significant direct effect on the working happiness of the elderly in career groups (b = 0.16, p < .05), 2) Social support within the career groups has a significant direct effect on the working happiness of the elderly in career groups (b = 0.44, p < .01) but does not have a significant indirect effect on the working happiness of the elderly in career groups (b = 0.17, p = .14), and 3) Positive psychological capital does not have a significant direct effect on the working happiness of the elderly in career groups (b = 0.14, p = .28) but has a significant indirect effect through the perception of self-efficacy in work on the working happiness of the elderly in career groups (b = 0.52, p < .001). Moreover, the perception of self-efficacy in work and social support within the career groups as well as positive psychological capital could explain the variations of the working happiness of the elderly at 16.5 percent.